The Unlocking Value: The Impact Of Investment Opportunity Set And Corporate Governance - Supriatiningsih Supriatiningsih; Pandaya Pandaya; Ramayuli Ramayuli; Aulia Maharani (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study examines the impact of corporate governance and investment opportunity set (IOS) on firm value in the banking sector listed on the Indonesia Stock Exchange (IDX) during the period of 2018-2022, using a sample of 18 companies and 90 observations. The focus of this research is to identify the roles of managerial ownership, board size, and audit committee in influencing corporate performance. The results show that managerial ownership and board size positively affect firm value, while IOS and the number of audit committees have no significant impact. This research contributes to the literature on corporate governance in Indonesia, providing insights into how these factors influence corporate performance, and serves as a foundation for further studies aimed at improving corporate governance structures in the Indonesian banking sector   Keywords: Investment Opportunity Set, Managerial Ownership, Number of Board of Commissioners, Audit Committee, Firm Value